(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research intends to show the internal determinants and to evaluate and measure their impact on commercial bank profitability, as internal determinants are key and influential indicators on Joint Stock companies performance that are within their control and management. The bank’s size) as internal factors have become a concern for them in view of the quick changes and advances in the banking world and its technologies. As a result, for the period 2015-2020, this research was applied to a sample of Joint Stock companies listed in the Iraqi market for securities, represented by the selection of (13) banks, namely Ashur, Baghdad, Iraqi commercial, investment, Iraqi Gulf, international development, Sumer, Mosul, Mansour, Al-Ahly of Iraq, Al-Mutated, Middle East, and used the descriptive analytical approach of the research variables available in the research sample banks in order to Return on deposits, rate of return on available money (as calculated by the statistical tool EViews V9), and use of panel data analysis according to the three models (accumulation regression model, fixed-effects model, random-effects model) according to this analysis, which will cover the research period (2015-2020). With the research sample represented by (13) banks. Through the application of tablet data, it was discovered that the internal determinants do not significantly affect the profitability ratios or the dependent variable at a significant level of 5 and 10%/4, respectively, whereas the aggregate model was significant and more appropriate according to the restricted f test, i.e. accepting the fifth hypothesis and vice versa if it was rejected. The constant is preferable, but if the Hausman test discovered a Chi-sq value less than the tabular at the 5% level, then this model is preferable to the constant, i.e. the rejection of the sixth hypothesis, and if the coefficient of determination was stronger and significant in the fixed model. than the random model It is more likely and appropriate according to these results.